(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Abu Rayhan Beruni was a great thinker and medieval scientist-encyclopedist, astronomer, mathematician, philosopher, geographer, ethnographer, anthropologist, geologist, historian, botanist, pharmacologist and humanist, who made a huge contribution to the development of world science and civilization. In this article, the worldview and some historical and philosophical concepts of al-Beruni, the thinker of the encyclopedic mind, are analyzed logically and ontologically: in particular, the concepts of: “natural philosophy”; “nature; “”reason”; “thinking”; “time”; “matter and form”; “cause and effect”; “possibility and reality”; “necessity and chance”. In conclusion, the article states: despite the fact that Al-Beruni’s thought was expressed more than a thousand years ago, some of his ideas still remain relevant and consonant with modernity.